Study for using value engineering and application in projects of ALanbar government (Iraqi Journal of Civil Engineering, 2012)
Value Engineering is one technique to distributed the resources fairly and perfect progress with honest meaning to decrease the expenditure , perform functions to improve the value element in project through decreasing the cost and developing the quality as well as choosing the better alternative to get the best quality . The research studies the value engineering technique by a field surveying and questionair submitted to different project personal in ALanbar government trough many stages beginning primary and finial design to construction project stage and the last operating and maintenance stage. Many site visits and personal interviews were carried out with their actual onsite experience on some of construction projects. Many useful conclusions and recommendations, one of them the researcher recommended to use the value engineering in contracts which have been support the economic national and save money to finance other projects.